Application Of Diadynamic Currents To Reduce Pain - Amalia Solichati Rizqi (Poltekkes Kemenkes Semarang, 2021)
Background: Pain has become a separate complaint or disease, not only as a means of protecting the body or a symptom of other diseases. With increasing age, a person will experience a decrease in physiological functions that can affect the system in the body. Diadynamic currents are part of electrecal stimulation which has a low frequency function to reduce pain.Methods:This is an experimental research with a quantitative approach. The sampling technique used nonprobability sampling based on the inclusion and exclusion criteria. The data analysis used was non-parametric statistics, namely by using the Wilcoxon signed rank test.Results: Based on the result of the Wilcoxon test showed that the value. Sig. is 0.000, which is less than 0.05. By giving a diadynamic current, the pain felt by someone will be reduced.Conclusion: diadynamic currents can be used to reduce pain